(3GdOQLGJ GdYdjI aj WHbGJ GdYdeGA GdMfajIs - (3eMeO Hf eMeO Hf eMeO Hf Ydj Hf jhSa, CHh GdNjQ, TeS GdOjf, GdYeQj GdOeTbqj Ke GdTjQGRj GdTGaYqj, GdTgjQ HGHf GdLRQj , J (B833 (3g` s; (3GdJbj GdZRj , Jbj GdOjf Hf YHO GdbGOQ GdJejej GdZRj,J (B1010 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd GdNdb WHbGJ s
(3BNQgG (B:s
(3CHh YHO Gddg GdRYaQGfi GdPi QJH eSGFd GdLGeY GdcHjQ s
(3QJH GdCSeGA Ydi GdMQhas
(3GdLRA GdCNjQ ef GdfSNIs
(3JHUQI GdYfhGf (B:s
(3JgPjHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B85 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B91s
Keywords: (3GdJGQjNs